2016
DOI: 10.1038/srep38468
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-modified G4-decoy oligonucleotide anchored to nanoparticles: delivery and bioactivity in pancreatic cancer cells

Abstract: KRAS is mutated in >90% of pancreatic ductal adenocarcinomas. As its inactivation leads to tumour regression, mutant KRAS is considered an attractive target for anticancer drugs. In this study we report a new delivery strategy for a G4-decoy oligonucleotide that sequesters MAZ, a transcription factor essential for KRAS transcription. It is based on the use of palmitoyl-oleyl-phosphatidylcholine (POPC) liposomes functionalized with lipid-modified G4-decoy oligonucleotides and a lipid-modified cell penetrating T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 39 publications
(85 reference statements)
0
27
0
Order By: Relevance
“…Chemical modifications, on the other hand, employed hydrophobic interactions or covalent ligations to introduce chemical ligands or functional molecules onto exosomal surfaces. 2123 However, hydrophobic probes are randomly inserted on exosome surfaces, and thus lack of precision and specificity. And that covalent ligations usually requires harsh conditions for chemical reactions, which could possibly affect the structure and function of exosomes and give rise to safety concerns.…”
mentioning
confidence: 99%
“…Chemical modifications, on the other hand, employed hydrophobic interactions or covalent ligations to introduce chemical ligands or functional molecules onto exosomal surfaces. 2123 However, hydrophobic probes are randomly inserted on exosome surfaces, and thus lack of precision and specificity. And that covalent ligations usually requires harsh conditions for chemical reactions, which could possibly affect the structure and function of exosomes and give rise to safety concerns.…”
mentioning
confidence: 99%
“…In contrast, replacement of both TT loops with H 15 resulted in ΔT m = +0.6°C, which might refer to stacking interactions of H 15 moieties over the underlying G-quartet according to molecular modeling studies. [5,57,58] Molecular modeling suggests that such significant increases could be a result of stacking interactions between two anthraquinone monomers.…”
Section: Discussionmentioning
confidence: 99%
“…xenograft mice [113]. Moreover, the authors subsequently reported a lipid-modified strategy based on the use of palmitoyl-oleyl-phosphatidylcholine liposomes, which improved the delivery of the G4-decoy by coupling to the liposomes efficiently, resulting in decreased Kras transcription levels and metabolic activity of pancreatic cancer cells [114].…”
Section: Decoysmentioning
confidence: 99%